2022
DOI: 10.1038/s41598-022-09648-1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous adsorption of As(III) and Cd(II) by ferrihydrite-modified biochar in aqueous solution and their mutual effects

Abstract: A simply synthetic ferrihydrite-modified biochar (Fh@BC) was applied to simultaneously remove As(III) and Cd(II) from the aqueous solution, and then to explore the mutual effects between As(III) and Cd(II) and the corresponding mechanisms. The Langmuir maximum adsorption capacities of As(III) and Cd(II) in the single adsorbate solution were 18.38 and 18.18 mg g−1, respectively. It demonstrated that Fh@BC was a potential absorbent material for simultaneous removal of As(III) and Cd(II) in aqueous solution. Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The high-resolution spectra of Fe2p3 showed that Fe had three sets of double peaks in all four minerals, and no new peaks appeared or changes in binding energy occurred before and after the adsorption of Cd, demonstrating that the morphology of the adsorbent did not change during the adsorption process. The proportion of the Fe2p3 peak area in FH and Fe-OM did not change significantly before and after Cd adsorption, suggesting that the adsorption of Cd by these four adsorbents does not depend on Fe, which is consistent with the conclusion obtained by Tian et al [ 74 ] in studying the adsorption of Cd on the complex of pyrite and biochar.…”
Section: Resultssupporting
confidence: 90%
“…The high-resolution spectra of Fe2p3 showed that Fe had three sets of double peaks in all four minerals, and no new peaks appeared or changes in binding energy occurred before and after the adsorption of Cd, demonstrating that the morphology of the adsorbent did not change during the adsorption process. The proportion of the Fe2p3 peak area in FH and Fe-OM did not change significantly before and after Cd adsorption, suggesting that the adsorption of Cd by these four adsorbents does not depend on Fe, which is consistent with the conclusion obtained by Tian et al [ 74 ] in studying the adsorption of Cd on the complex of pyrite and biochar.…”
Section: Resultssupporting
confidence: 90%
“…In this context, several adsorbents have been developed and tested for their efficiency in removing different pollutants [ 6 , 12 , 29 ]. The dynamic adsorbents are based on activated carbon [ 30 ], activated alumina [ 31 ], inorganic minerals [ 32 ], biomass adsorbents [ 33 , 34 , 35 , 36 , 37 , 38 ], polymer [ 39 , 40 , 41 ], carbon nanotubes (CNTs) [ 42 , 43 , 44 ] graphene oxide [ 45 , 46 ], metal-organic frameworks [ 47 ], microplastics [ 48 ] and more. Among these, CNTs based adsorbents are particularly interesting because their unique physical and chemical properties are relevantly suitable for adsorption [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferrihydrite-modified biochar (Fh@BC) was utilized for the simultaneous decontamination of As( iii ) and Cd( ii ) ions from binary-metal aqueous systems as well as determine the mechanism of the sorption process. 95 The Langmuir model best correlated with equilibrium sorption data with optimum sorption rates of 18.38 and 18.18 mg g −1 for As( iii ) and Cd( ii ), respectively. The mechanisms of the simultaneous elimination of As( iii ) and Cd( ii ) by Fh@BC were due to cation exchange, complexation, and oxidation.…”
Section: Competitive Decontamination Of Heavy Metals From Sorption Sy...mentioning
confidence: 92%